Soft segment length controls morphology of poly(ethylene oxide) based segmented poly(urethane-urea) copolymers in a binary solvent - Avaz, Senem; Oğuz, Oğuzhan; Kurt, Hasan; Menceloğlu, Yusuf Ziya; Atılgan, Canan (Elsevier Science Bv., 2017)
It is known that morphology and structure-property behavior of poly(ethylene oxide) (PEO) based poly (urethane-urea) copolymers are affected by soft segment (SS) chain length. Here, a multi-scale computational study is carried out to determine the origins of this behavior, supported by atomic force microscopy (AFM) imaging. First, single PEO chains of varying lengths are comparatively examined by molecular dynamics and dissipative particle dynamics (DPD) simulations in THF: DMF solvent mixture to verify that the coarse graining strategy is applicable to the system at hand. In the second step, hard segment (HS) beads are attached to PEO chains to study their effect on the overall morphology. We find that the critical chain length of PEO plays a key role on the structure-property behavior of these copolymers. Density fields obtained from DPD calculations reveal a stable channel formation by SS beads in the copolymers if their length is below a threshold value. HS-SS interactions drive this behavior by promoting phase mixing. The role of the binary solvent is essential as the channel-like structures are not stable in the pure solvents. In contrast, for chains having long enough PEO segments, spontaneous clustering of the PEO units controls morphology development. This behavior gives rise to the formation of globular SS clusters surrounded by HS units. The dual solvent acts as a lubricant, with THF preferring the PEO clusters. Results obtained from DPD studies are corroborated by AFM images obtained for the corresponding copolymers. The strategy employed lays the foundations for developing systems having novel morphologies and macroscopic-properties using designs based on HS-SS cooligomers.
WOS: 000410617000008
Keywords: Thermoplastic Polyurethanes; Molecular Dynamics; Dissipative Particle Dynamics; Reverse Mapping; AFM